Early Turonian ammonites from Goulmima, southern Morocco - Kennedy, W; Gale, A; Ward, D; Underwood, C (2008)
In recent years, large numbers of Early Turonian ammonites from Morocco have found their way onto the open market. They come from the Cretaceous escarpment to the north of Goulmima, in the province of El Rachidia, southern Morocco. A section measured northeast of the village of Asfla sets the ammonites in stratigraphic context. The fauna belongs to the widely recognised upper lower Turonian Mammites nodosoides Zone, and comprises Romaniceras (Yubariceras) reymenti (COLLIGNON, 1967), Mammites nodosoides (SCHLÜTER, 1871), Nannovascoceras intermedium RENZ and ALVAREZ, 1979, Fagesia peroni PERVINQUIÈRE, 1907, Neoptychites cephalotus (COURTILLER, 1860), Neoptychites aff. hottingeri COLLIGNON, 1967, Choffaticeras (Choffaticeras) segne (SOLGER, 1903) and Wrightoceras munieri (PERVINQUIÈRE, 1907).